CBK searching (chemistry-biology-keyword): Performing cross-discipline collaborative searches. (June 2015) - Miller, Kimberly; Mendelson, Seth
Abstract: A debate over whether a search is a chemistry or a biology search is becoming increasingly more frequent within search teams. The line between non-text chemistry and biology searching has become blurred in recent years. The appearance of "non-natural" amino acids and modified peptides, for example, has given rise to the questions: Is it a structure? Is it a sequence? Could it be both? It may not be a question of one or the other, but perhaps working with a colleague to bring the best possible answer to the client. Several examples clarify the line and present guidance when beginning a search. Consider the size of the molecule, how many amino acids are present and what the client needs in order to best cover all bases and create a more comprehensive search report.